PEMBUATAN ETIL ASETAT DARI HASIL HIDROLISIS, FERMENTASI DAN ESTERIFIKASI KULIT PISANG RAJA (Musa paradisiaca L.) - Sari Liza Azura Nst; Reni Sutri; Iriany (Talenta Publisher (Universitas Sumatera Utara), 2015)
Ethyl acetate is a clear liquid, colorless, smelling typical which commonly used as a flavor enhancer. Banana peels contain high valuable components, such as carbohydrates, vitamin C, calcium and other nutrients. The purpose of this study was to utilize the ‘raja’ banana peel waste (Musa paradisiaca L.) in the making of ethyl acetate. Variations in this experiment is comparison of raw materials and water 1: 4; 1: 7; 1:10 and hydrolysis temperature of 50oC, 60oC, 70oC. At first banana peel was scraped, dried and mashed to make banana peel powder.The content of carbohydrates in the ’Raja’ banana peel powder is 45.21% (w/w). Banana peel powder was hydrolyzed into water for 180 minutes using acid hydrocloric acid as catalist. The hydrolysis product was fermented for 24 hours using instant yeast 'Fermipan' and then was distilled. The Distillation product was esterified with acetic acid and hydrochloric acid as catalyst for 15 minutes at 60°C. The influence of various process variables were observed in this experiment. The maximum ethyl acetate yield was obtained 70.377% at condition of raw materials and water ratio = 1:10 and hydrolysis temperature of 50oC. The results obtained in this experiment showed that the ‘raja’ banana peel can be used as an alternative raw material which low cost and easy to obtain to produce ethyl acetate.